Pengaruh Tekanan, Peluang, Rasionalisasi dan Nilai Etika terhadap Intensi Kecurangan Karyawan: Studi Kasus pada Perusahaan BUMN - Riski Hildayani; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the effect of pressure, opportunity, rationalization, and ethical values on employee fraud intentions in BUMN in Indonesia. This type of research is classified as survey research with a quantitative approach. The population in this study were employees of BUMN in Indonesia. The research sample was determined by purposive sampling method in order to obtain a sample of 65 employees in BUMN. The type of data used is primary data obtained from questionnaires. Data analysis using multiple regression, employee fraud intention as the dependent variable and pressure, opportunity, rationalization and ethical values as independent variables. The result of this study indicate that: (1) pressure has no positive significant effect on employee fraud intention, so hypothesis 1 is rejected, (2) opportunity has a significant positive effect on employee fraud intention, sho hypothesis 2 is accepted, (3) rationalization has a significant positive effect on employee fraud intention employee fraud, so hypothesis 3 is accepted, (4) ethical values do not have a significant negative effect on employee fraud intentions, so hypothesis 4 is rejected. So, it can be concluded that opportunity and rationalization have a significant influence on employee fraud intentions in BUMN.